Date palm biotechnology - Jain, Shri Mohan; Al-Khayri, Jameel M.; Johnson, Dennis V. (Springer eBooks., 2011)
This important reference book is the first comprehensive resource worldwide that reflects research achievements in date palm biotechnology, documenting research events during the last four decades, current status, and future outlook.  It brings together the principles and practices of contemporary date palm biotechnology. The book is essential for researchers, policy makers, and commercial entrepreneurs concerned with date palm. It is invaluable for date palm biotechnology students and specialists. This monumental work is written by an international team of experienced researchers from both academia and industry.  Each chapter contains background knowledge related to the topic, followed by a comprehensive literature review of research methodology and results including the authors' own experience and supported with illustrative tables and photographs. In addition to an introductory chapter, the book consists of thirty two review chapters highlighting progress and current research status covering various aspects of date palm biotechnology in five sections: A) Discuss the research development, methodology, and commercial application of micropropagation  in seven chapters, B) Deal with the research development and applications of somaclonal variation and mutation in date palm, covered in seven chapters, C) Describe the status of date palm germplasm and current techniques employed in conservation and molecular characterization are described in seven chapters, D) Address research progress made in date palm genetics and breeding in eight chapters, E) Describe up-to-date progress made in metabolites and industrial biotechnology in three chapters.